ЗАРАФШОН ВОҲАСИ ДЕҲҚОН ЖАМОАЛАРИ ВА ЧОРВАДОРЛАР МАДАНИЯТЛАРИНИНГ ЎЗАРО АЛОҚАЛАРИ (Scientific journal of the Fergana State University, 2023)
This article is devoted to the correlations between Zarafshan oasis peasant communities and cattle-breeders' culture on  basis of the theoretical experiment results. The main attention is pointed to Sarazm, Zamonbobo and Toqaytepa memorials and cattle-breeders’ culture affections to their formations and developments.